2018
DOI: 10.19166/med.v5i1.1178
|View full text |Cite
|
Sign up to set email alerts
|

Il-4: Prediktor Anti Inflamasi Pada Stroke Iskemik ?

Abstract: <p>The brain ischemia due to vascular occlusion, especially in the main cerebral artery, could trigger the microglia as a natural immune cell in the brain. These activated microglia will turn up the inflammation cascade in the ischemic area. Interleukin-4 (IL-4) has a vital role in the microglial alteration to become an anti-inflammatory phenotype, which wind up the expression of MHC II and CD11c. Moreover, previous studies has supported that the stimulation of IL-4 in the culture of microglia/macrophage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…The results of the study showed that the majority of respondents' length of stay in this study was 1-5 days, as many as 19 people (63.3%). The results of this study are in line with the results of research conducted by [7] which states that the length of stroke patient care is in a total of days. Respondents who had a stroke were treated for at least 4 days and the longest being treated at 15 days.…”
Section: Methodssupporting
confidence: 89%
“…The results of the study showed that the majority of respondents' length of stay in this study was 1-5 days, as many as 19 people (63.3%). The results of this study are in line with the results of research conducted by [7] which states that the length of stroke patient care is in a total of days. Respondents who had a stroke were treated for at least 4 days and the longest being treated at 15 days.…”
Section: Methodssupporting
confidence: 89%